India-Pakistan relations common ground and points of discord - Ashraf, Sajjād (Emirates lecture, 2011)
Pakistan and India, the two largest countries in the Sout Asian region, share more than just a common border; they also share a common history, culture, language, and -- at certain levels -- a common ideology. Yet they remain enemies who have fought several wars, face seemingly insurmountable geographic issues, and co-exisst amid discord on several fronts ... In this paper I aim to highlight how, among the many points of discord, these shared factors could -- and should -- be seen as rays of light in an unnecessarily dark relationship